Distinctive Features of the Development of Professional English Speaking Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the distinctive features of professional English speaking skills development, highlighting key factors that differentiate it from general English acquisition. We analyze the roles of specific vocabulary, register, fluency, and cultural awareness in successful professional communication. Additionally, we examine the impact of context, audience, and purpose on effective spoken English in professional settings. The article concludes by outlining practical strategies for enhancing professional English speaking skills and the importance of ongoing development in this domain.